(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: A disorder characterized by airway obstruction and breathing difficulty is known as chronic obstructive pulmonary disease. Fatigue is one of the typical signs and symptoms of COPD. Fatigue is the term used to describe a persistent feeling of exhaustion, and it can have a significant negative influence on person’s capacity to carry out everyday tasks. Purpose: The purpose of this study is to analyze how low impact aerobic training and upper limb strengthening exercise is effective in dyspnea and fatigue level among individuals with COPD. Materials and Methods: The 106 subjects were selected based on inclusion and exclusion criteria from Hepziba Chest Clinic and Spirometry centre, Nagercoil. The pre and post-test values were measured using the BORG scale and Fatigue Severity Scale. The subjects were allocated into two groups. Low impact Aerobic training group:(n=53) received aerobic training with conventional exercise and Upper limb strengthening group:(n=53) received upper limb strengthening exercise with conventional exercise. The study was done for four weeks. The entire procedure was performed from October 2022 to july 2023 Results: When comparing the low impact Aerobic training group with upper limb strengthening group, the low impact Aerobic training group indicates significant (p<0.0001) effect in lowering the fatigue level as assessed by Borg scale and Fatigue Severity Scale. Conclusion: The study concluded that Low impact Aerobic training had a significant effect compared to upper limb strengthening exercise on Dyspnea and Fatigue Severity Scale among individuals with COPD.